Tadeusz T. Gudzowski Exlibris / [Vilnis Resnis]. - Resnis, Vilnis (1939-2002) ([wydawca nieznany], 1980)
Przedstawia żaglówkę i lecące ptaki, napis u góry na wstędze: Tadeusz T. Gudzowski, u dołu: Exlibris.